2014
DOI: 10.1155/2014/145901
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Hexane Extract of Phalaris canariensis on High Fat Diet‐Induced Obese and Streptozotocin‐Induced Diabetic Mice

Abstract: Obesity is one of the major factors to increase various disorders like diabetes. The present paper emphasizes study related to the antiobesity effect of Phalaris canariensis seeds hexane extract (Al-H) in high-fat diet- (HFD-) induced obese CD1 mice and in streptozotocin-induced mild diabetic (MD) and severely diabetic (SD) mice.AL-H was orally administered to MD and SD mice at a dose of 400 mg/kg once a day for 30 days, and a set of biochemical parameters were studied: glucose, cholesterol, triglycerides, lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…These results suggest that DLE may ameliorate HFD-induced hepatic steatosis through inhibition of oxidative stress. In previous studies, plant extracts have been reported to protect against obesity-induced oxidative damage in mice (41,42). Our previous study also demonstrated that DLE protects against UVB-induced oxidative damage and acetaminophen-induced oxidative liver damage in mice (38,43).…”
Section: Discussionmentioning
confidence: 65%
“…These results suggest that DLE may ameliorate HFD-induced hepatic steatosis through inhibition of oxidative stress. In previous studies, plant extracts have been reported to protect against obesity-induced oxidative damage in mice (41,42). Our previous study also demonstrated that DLE protects against UVB-induced oxidative damage and acetaminophen-induced oxidative liver damage in mice (38,43).…”
Section: Discussionmentioning
confidence: 65%
“…The induction of obesity in animals via HFd supplementation is the most popular means of mimicking obesity in human, and a number of studies have been conducted using HFd-induced obese mouse models, in which HFd supplementation increases abdominal fat and body weights (22). Previous studies have reported crude plant extracts and natural compounds isolated from them induce weight loss and prevent diet-induced obesity (17,23).…”
Section: Discussionmentioning
confidence: 99%
“…Protocatechuic acid (PCA) is a phenolic compound, the main metabolite of anthocyanin, which has been reported to display various pharmacological properties 7 . In the present investigation, we proposed the hypothesis that PCA exerts antiobesity, antihyperlipidemic, antidiabetic effects in the high fatty diet with a low dose of alloxan-induced in diabetic rats 8,9,10,11 .…”
Section: Hfd Compositionmentioning
confidence: 93%
“…(6) Containing lard oil (25%), fructose (40%), protein powder (45%), cholesterol (2%), vitamin and fiber contains feed. Obesity is more likely to increase the risk for hyperglycemia because of alteration in serum lipid profile like Serum Insulin level or blood glucose level 8 . Generally, a high-fat diet is one of the major factors causing obesity and that the longterm intake of high-fat diet evokes a significant increase in abdominal fat weight.…”
Section: Hfd Compositionmentioning
confidence: 99%